Mengenal gambaran ultrasound lesi jinak, ganas dan metastasis pada nodus limfa leher menggunakan ultrasonografi - Epsilawati, Lusi; Polii, Hendra; Herawati, Erna (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI); Vol 3 No 3 (2019): Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: This study is aimed to review the ultrasound imaging (USG) of benign, malignant and metastases lesions in cervical lymph nodes. Literature Review: This article was written based on some scientific literatures in which will explain the interpretation technique and imaging characteristic to distinguish between benign, malignancies and metastases lesions in cervical lymph nodes through ultrasound imaging. There are many pathological conditions may occur in cervical lymph nodes that can be analyzed in ultrasound. The signs of benign, malignant and metastases lesions in cervical lymph nodes, all may have different characteristics. Those characteristics could help the practitioners and radiologists to distinguish the lesions based on several assessment categories. Hopefully, the reader of this article could understand the technique to distinguish benign, malignant and metastases lesions in neck lymph nodes in ultrasound. Conclusion: Ultrasonography is the most commonly used modality for lymph nodes examination, although the accuracy cannot be trusted or guaranteed 100% but this modality always be used and becoming one of all choices. Through the ultrasound, it could be concluded that some of the characteristics of the assessment can be a guide to distinguish benign, malignant and metastases lesions in cervical lymph nodes.